2018
DOI: 10.1530/eje-17-1063
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum and non-post-partum relapsing Graves’ hyperthyroidism display different response to anti-thyroid drugs

Abstract: Relapsing Graves' hyperthyroidism in the PP period is more prone to undergo a remission after a second course of MMI treatment. In these patients, a conservative therapeutic approach is more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another study found different responses to re-treatment between those who had a recurrence in the postpartum period vs. those whose GD recurred outside the postpartum setting. In a retrospective study of 43 women of childbearing age with GD recurrence, those who relapsed in the post-partum period were more likely to undergo remission with a significant reduction in TRAb levels, compared to those who relapsed outside of the post-partum period (79 vs. 32%%) [45].…”
Section: Postpartum Graves' Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…Another study found different responses to re-treatment between those who had a recurrence in the postpartum period vs. those whose GD recurred outside the postpartum setting. In a retrospective study of 43 women of childbearing age with GD recurrence, those who relapsed in the post-partum period were more likely to undergo remission with a significant reduction in TRAb levels, compared to those who relapsed outside of the post-partum period (79 vs. 32%%) [45].…”
Section: Postpartum Graves' Diseasementioning
confidence: 97%
“…Up to 20-30% of women treated with anti-thyroid drugs are able to stop antithyroid drug therapy by the third trimester [40]. Several studies have demonstrated that the rebound of immunity in the postpartum period is associated with new-onset GD [41][42][43] or recurrence of GD [44,45], although this finding has not been universal [46]. A retrospective analysis reported that for parous women 45% of GD had its onset in the postpartum period, while the onset occurred in subsequent years for the other 55% [41].…”
Section: Postpartum Graves' Diseasementioning
confidence: 99%
“…Postpartum‐associated rebound immune phenomena may also favor relapse of hyperthyroidism [117, 118]. Among women in remission after ATD treatment, relapse occurred more frequently in women who then had a successful pregnancy than in those who had no pregnancy [119], although women with hyperthyroidism relapsing in the postpartum period had a greater decrease in TSHR‐Ab levels and a higher rate of remission compared to women whose relapse of hyperthyroidism was independent of pregnancy/being postpartum [120]. As far as GO is concerned, no differences in GO prevalence and degree of severity were found in women whose hyperthyroidism relapsed in the postpartum period [120].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a specifically designed study compared the clinical and biochemical phenotype of patients with relapsing Graves' hyperthyroidism according to a PP and a non-PP (NPP) onset. The results demonstrated an overall identical phenotype as assessed by superimposable FT3, TRAb titers, thyroid volume, smoking habit, presence, and degree of orbitopathy at diagnosis of relapse independently of a PP or NPP onset (25). More importantly, despite similar starting dose of MMI and duration of treatment, patients with a PP relapse were characterized by a strikingly higher success rate of MMI as opposed to those with NPP relapse (79% vs. 32%).…”
Section: Peculiar Aspects Of Pp Relapses Of Gdmentioning
confidence: 76%